2016
DOI: 10.1021/acs.chemrev.5b00485
|View full text |Cite
|
Sign up to set email alerts
|

Li+Catalysis and Other New Methodologies for the Radical Polymerization of Less Activated Olefins

Abstract: After a brief survey of conventional radical polymerization of alkenes, we review their Li(+) catalyzed radical polymerization and their controlled radical polymerization. Emphasis is on homopolymerization, but related copolymerization of less activated monomers is mentioned as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 148 publications
0
28
0
Order By: Relevance
“…[56] Li + catalyzed radical polymerizations have been explored as an alternative route to radical polymerization of certain olefins such as isobutylene. [57] In order to attain control of molecular weight distribution and macromolecular architectures,c opolymerization of olefins and polar monomers has been attempted via reversibledeactivation radical polymerization (RDRP) techniques, ag roup of radical polymerization processes which rely on reversible formation of dormant states to minimize radicalradical termination reactions and give each initiating radical an equal chance of propagating with monomer. [58] Although RDRP techniques have been demonstrated to be incredibly versatile,a ble to synthesize aw ide range of macromolecular architectures under various conditions, [59] they have had limited success in copolymerizing olefins.T he main reason for this is that the rate of reactivation from the dormant state is very low when an olefin is on the chain end due to the lack of radical-stabilization provided by olefins compared to polar monomers such as (meth)acrylates.…”
Section: Free Radical Polymerization Of A-olefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[56] Li + catalyzed radical polymerizations have been explored as an alternative route to radical polymerization of certain olefins such as isobutylene. [57] In order to attain control of molecular weight distribution and macromolecular architectures,c opolymerization of olefins and polar monomers has been attempted via reversibledeactivation radical polymerization (RDRP) techniques, ag roup of radical polymerization processes which rely on reversible formation of dormant states to minimize radicalradical termination reactions and give each initiating radical an equal chance of propagating with monomer. [58] Although RDRP techniques have been demonstrated to be incredibly versatile,a ble to synthesize aw ide range of macromolecular architectures under various conditions, [59] they have had limited success in copolymerizing olefins.T he main reason for this is that the rate of reactivation from the dormant state is very low when an olefin is on the chain end due to the lack of radical-stabilization provided by olefins compared to polar monomers such as (meth)acrylates.…”
Section: Free Radical Polymerization Of A-olefinsmentioning
confidence: 99%
“…Although ethylene can be successfully polymerized by free radical polymerization, homopolymerization of α‐olefins is severely limited, which is attributed to a high rate of degradative chain transfer of allylic hydrogens . Li + catalyzed radical polymerizations have been explored as an alternative route to radical polymerization of certain olefins such as isobutylene …”
Section: Radical Polymerization: a Limited Approach To Copolymerize Omentioning
confidence: 99%
“…In free‐radical polymerization, the propagating species is the long‐chain free radical that is generated by the attack of free radicals from initiators. These unstable initiators make the process very unpredictable and uncontrollable . Hence, living radical polymerization (LRP) was adopted in a bid to circumvent the existing limitations .…”
Section: Polymerization Techniquesmentioning
confidence: 99%
“…These unstable initiators make the process very unpredictable and uncontrollable. [67] Hence, living radical polymerization (LRP) was adopted in a bid to circumvent the existing limitations. [68] The usage of LRP is of great convenience as it reduces the need for strict purification of the reactants and allows the utilization and presence of different functional groups during and after the polymerization process.…”
Section: Polymerization Techniquesmentioning
confidence: 99%
“…This is mainly due to two reasons:1 )Ast he polyethylenyl radical is unconjugated and does not bear any stabilizing groups,the reversible activation of the dormant (reversibly deactivated) polymer species, which is essential for CRPs,d oes not occur readily;a nd 2) many CRP systems and their experimental setups are incompatible with the high temperatures (200-300 8 8C) and pressures (1000-4000 bar) conventionally believed to be necessary for an effective radical polymerization of ethylene. [24][25][26] Providing abasis for the present study,in2009, one of the authors revisited milder conditions for ethylene radical polymerizations and demonstrated that they can be effective also at less than 80 8 8Ca nd less than 250 bar if the solvent system is chosen wisely. [27][28][29] These conditions were subsequently applied using RAFT with xanthates as chain-transfer agents (CTAs), which yielded the first radical polymerization of ethylene with chain-growth-controlled characteristics.…”
mentioning
confidence: 94%